Inovasi Pelayanan Publik dalam Pembuatan E-KTP di Indonesia - Feby Hidayat (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This paper discusses service innovation in making e-KTP in Indonesia. Good public services can be seen and approved by the implementation in accordance with service standards. To achieve a good service standard is needed in public organizations. Public service innovations have now become what must be done by service providers, both in the level of the central government or regional governments. Every government is required to improve community services to the community in the form of existing innovations. The goals expected by public organizations can be used effectively and efficiently. The purpose of this article is to promote several types of public services in making e-KTP in Indonesia. The method used in this article is qualitative research with descriptive studies. The technique of taking data is based on library research and collecting data from online journals. The conclusion obtained is that which is expected to lead to the theory of service standards, namely procedures, completion time, service costs, service products, infrastructure and infrastructure, as well as maximum competency of service providers.